Phytoremediation of Three Heavy Metals Using Duckweed (Lemna minor): Fitoremediasi Tiga Logam Berat Menggunakan Duckweed (Lemna minor) - Ali, Huda Hilo; Alzurfi, Sadiq Kadhum Lafta; Aldujaili, Nawfal hussein kudhair (Universitas Muhammadiyah Sidoarjo, 2024)
Today, the world faces the problem of water pollution with heavy metals, which have toxic effects on living organisms, including humans. Treating this water pollution requires using low-cost, environmentally friendly techniques. Therefore, we selected the Lemna minor plant to investigate its capacity to phytoremediate some heavy metals in a laboratory. Three harmful metals for the aquatic environment were chosen: nickel (1, 5, and 10 ppm), cadmium (0.5, 2, and 4 ppm), and lead (0.5, 5, and 10 ppm), in addition to a control group. Removal ratio, relative growth rates (RGR), and bioconcentration factor (BCF) were measured under controlled light and temperature conditions. The highest removal efficiencies by Lemna minor of Cd, Pb, and Ni ranged between 92% (at 0.5 ppm), 99.7% (at 0.5 ppm), and 99.75% (at 1 ppm), respectively. The lower ratio recorded 28.6% in 10 ppm on the 1st day. The bioconcentration factor (BCF) for each metal per unit (kg/L) was recorded as follows: 10,550 for cadmium on the 14th day at 0.5 ppm, 385,352 for nickel at 1 ppm on the 21st day, and 484,382 for lead at 0.5 ppm on the 21st day. The results show significant varying effects of cadmium, nickel, and lead on the removal ratio and relative growth rate of organisms in the closed system. Further analysis is needed to understand the long-term effects and determine the precise mechanisms responsible for these different responses.These results suggest that L. minor is a suitable candidate for the removal of heavy metals from polluted water bodies Highlights: Heavy metals pollute water, harming organisms. Lemna minor tested for Cd, Pb, Ni phytoremediation. High removal efficiency; suitable for eco-friendly water treatment. Keywords: BCF, Heavy metals, RGR,. Phytoremediation, Lemna minor.